A LACANIAN EXPLORATION OF IDENTITY, NEUROSIS, AND THE ARTIST IN JAMES JOYCE’S A PORTRAIT OF THE ARTIST AS A YOUNGMAN - Qazi, Khursheed Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study examines James Joyce’s A Portrait of the Artist as a Young Man, focusing on identity development, neurosis, and the artist’s connection with society. Using Lacan’s psychoanalytic theory, the researcher investigates Stephen Dedalus as a subject navigating the complex dynamics of selfhood, desire, and social alienation. This paper explores Stephen’s changing identity, shattered sense of self, and internal conflict between societal standards and the desire for artistic independence. The paper also talks about Stephen’s rejection of the Symbolic Order and his eventual acceptance of the artist’s function as a means of addressing the Lacanian Real, a domain beyond language and societal restrictions. Through this Lacanian lens, Joyce’s novel emerges as a profound narrative about the challenges of self-realization, the destructive power of desire, and the alienating effects of societal expectations on the artist.